pengaruh terapi musik instrumental terhadap kualitas tidur pada pasien post operasi yang mengalami gangguan tidur tahun 2020 - Putri, Nesri Aulia; Destiawan Eko Utomo (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
Sleep disorders or insomnia is the most common disorder experienced by all people in the world. According to survey conducted by Crampex 86% of people around the world have sleep disorders namely insomnia, such as in England alone as many as ten million prescription drugs have been written each year for people with sleep disorders. In Indonesia, the prevalence of insomnia sufferers is estimated at 10%, which means that of the total 238 million people in Indonesia, around 23 million suffer from insomnia. The objective of this research to determine the effect of instrumental music therapy on sleep quality in post-operative patients who experience sleep disorders. The method use analysis approach to analyze the data that the author will use, namely thematic analysis: simplified approach. The articles that the researcher will review are primary data. Researchers use databases such as Google Scholar, PubMed, Research Gate and Elsevier. The results based on a literature review of five inclusion articles that have been reviewed by the author, it was found that there was an influence between instrumental music therapy on sleep quality with an average p-value <0.050. The conclusion is music therapy can affect changes in the quality of sleep in a person especially in patients after undergoing surgery that has a sleep disorder, the use of music therapy can be recommended as an alternative / non-pharmacological intervention that can affect the sleep quality of someone who has a sleep disorder.